PENGEMBANGAN MEDIA PEMBELAJARAN SCRAPBOOK UNTUK MENINGKATKAN KARAKTER GOTONG ROYONG PADA MATA PELAJARAN PENDIDIKAN PANCASILA SISWA KELAS IV SEKOLAH DASAR - Alycia Resti Nurhaji; Titin Sunaryati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The age of elementary school children is an ideal time to use learning media, especially concrete media. This research aims to develop learning media in the form of scrapbooks to strengthen the character of mutual cooperation in grade IV students at SDN Cijengkol 02, Bekasi. Scrapbooks are considered effective as a learning medium because they can facilitate interaction between students and teachers and increase students' interest in learning. This research uses the Research and Development (RnD) method, which includes the stages of design, validation, and media effectiveness testing. The results of the study show that the use of scrapbooks as a learning medium can increase the active participation of students and strengthen the character of mutual cooperation in accordance with the Pancasila Education material. In addition, this media also offers creative and interesting alternatives in delivering material, so that the learning process becomes more interactive and fun.